ROLE OF ISLAMIC EDUCATION AND COMMUNITY VALUES AMONG INTERNATIONAL STUDENTS AT MUHAMMADIYAH UNIVERSITY SURAKARTA - Barry, Aboubacar; Salim, Hakimuddin; Azani, Mohammad Zakki (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Internationalizing Islamic higher education requires universities to cultivate enduring community values alongside academic excellence. This study examines the role of Islamic education in promoting community values among international students at Muhammadiyah University Surakarta, addressing what forms enact these values, which factors shape them, and what implications follow for belonging and participation. Using a qualitative descriptive design, we analysed interviews, focus group discussions, non-participant observations, and institutional documents. Participants were purposively selected to reflect diverse nationalities. Data were coded iteratively and thematically, with triangulation, peer debriefing, and reflections supporting trustworthiness. Findings show a three-channel ecosystem: formal curriculum linking theology, ethics, and jurisprudence to daily practice; extracurricular platforms (study circles and service) translating principles into action; and institutional culture embedding value-bearing routines. Four conditions influenced value formation: cultural diversity and peer interaction, dialogic pedagogy, institutional support systems, and language proficiency. These dynamics yielded transformative outcomes moral resilience in addressing dilemmas, social cohesion through a shared moral vocabulary of justice, compassion, and responsibility, and intercultural competence oriented to global citizenship. The study refines an integrative framework connecting curricular, co-curricular, and cultural channels to value internalization and identifies practical levers for inclusive design. Future research should test these pathways longitudinally and across Islamic university traditions.